506 An Audit of Documentation in Orthopaedic Trauma Meetings. (4th May 2021) - Jackson, T; Chahal, J
Abstract: The aim of this audit cycle is to assess departmental compliance with the standards elucidated by the Academy of Medical Royal Colleges, and the British Orthopaedic Association with respect to patient record keeping in regard to trauma meeting documentation. Specific criteria for the documentation of the information were devised from the audit standards. Over a one-week period in September 2019, patient notes from all Trauma and Orthopaedic the notes for all patients on the week's take lists were inspected for trauma meeting documentation from the following morning. A documentation proforma was then implemented and notes were then re-audited after 3 months of the intervention to assess its effect. Most patients had trauma meeting documentation however it often lacked significant information such as the take consultant, injury, date/mechanism of the injury as well as correct contact details. After implementation of the proforma, there was an improvement to 70% or above for documentation of significant information in almost all established criteria. Poor documentation often resulted in recurrent calls to the on-call team the following day to clarify diagnoses and plans which were often inadequate or unclear. This was improved through the introduction of a proforma to standardise the documentation present.